2015
DOI: 10.4274/tdd.2671
|View full text |Cite
|
Sign up to set email alerts
|

Malign Melanoma: Risk Factors and Major Clinical Findings

Abstract: Malign melanom (MM) insidansı en hızlı artan kanser türlerinden biridir ve deri kanserlerine bağlı ölümlerin önde gelen nedenidir. Buna karşın deri melanomu hastanın erken dikkatini çekerek hekime ulaşması durumunda çoğunlukla erken aşamada ortadan kaldırılır ve hastanın normal yaşamını sürmesi sağlanabilir. Melanom herkeste görülebilmekle birlikte açık ten rengi, yoğun ultraviyole maruziyeti, belirli bir genetik zemin (CDKN2A gen mutasyonu) bulunması, çok sayıda melanositik nevus bulunması ve displastik nevus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The primary risk factors include advanced age and a familial history of BC [5,6], and the accordingly implemented strategies of screening and early diagnosis have been associated with a reduced need for invasive intervention, increased overall survival, and decreased mortality [7,8]. The multiphase oncogenesis involves changes at the chromosomal level, polymorphism, angiogenesis, and uncontrolled cell growth that results in a tumor [9,10], with ongoing genetic mutations leading to invasion, metastasis, and resistance to treatment [11]. During all these phases, specific compounds are released from the cancerous cells in markedly increased amounts.…”
Section: Introductionmentioning
confidence: 99%
“…The primary risk factors include advanced age and a familial history of BC [5,6], and the accordingly implemented strategies of screening and early diagnosis have been associated with a reduced need for invasive intervention, increased overall survival, and decreased mortality [7,8]. The multiphase oncogenesis involves changes at the chromosomal level, polymorphism, angiogenesis, and uncontrolled cell growth that results in a tumor [9,10], with ongoing genetic mutations leading to invasion, metastasis, and resistance to treatment [11]. During all these phases, specific compounds are released from the cancerous cells in markedly increased amounts.…”
Section: Introductionmentioning
confidence: 99%
“…It is crucial for patients with risky nevi to have periodic dermatologic follow-ups. Additionally, it is especially important that these patients be instructed on how to perform SSE [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…CDKN2A, a tumour suppressor, and melanocortin-1 gene defects have been shown to cause genetic predisposidegree relatives of patients diagnosed with melanoma is very important for early diagnosis. It should be noted that familial melanomas may occur at an earlier age [8]. In a survey study investigating the frequency of screening among children of parents with a family history of melanoma, 28% of parents reported that children had received a skin exam by a healthcare provider in the past 6 months [16].…”
Section: Discussionmentioning
confidence: 99%
“…[4] Other risk factors include: skin type (fair skin), environmental factors (ultraviolet exposure), genetic basis (CDKN2A gene mutation), large number of previous melanocytic nevi, dysplastic nevus, and previous history of melanoma. [5] Types and clinical characteristics Incidence of mucosal melanoma, which originates from melanocytes located in mucosa lining the respiratory, gastrointestinal, and urogenital regions, is only about 1.4% among all melanomas. [6] Mucosal melanomas have relatively higher mortality rates compared to cutaneous melanomas.…”
mentioning
confidence: 99%
“…The first phase, known as the tumor's radial growth phase (in situ period) is followed by the vertical growth phase (invasive period) in which neoplastic cells cross the dermoepidermal junction and spread to the papillary dermis. [5] Nodular melanoma is accepted as having no radial growth phase and only vertical growth phase. [1] Superficial spreading malignant melanoma subtype is most common in fair-skinned individuals and accounts for 70% of all malignant melanomas.…”
mentioning
confidence: 99%